SAMHD1: a novel antiviral factor in intrinsic immunity. (September 2012) - Chen, Zhangming; Zhang, Linjie; Ying, Songcheng
Some intracellular/membranous factors exert intrinsic immunity against viral pathogens. Most recently, SAMHD1 has been shown to be one of these factors. SAMHD1 is a nucleus-localized protein, and mutations in the gene are associated with Aicardi–Goutières syndrome. As a triphosphohydrolase, it depletes the intracellular pool of dNTPs in myeloid cells, such as macrophages and dendritic cells, to a low level that establishes a precursor-deficient environment for the synthesis of lentiviral cDNA, thereby restricting viral replication in these host cells. However, some viruses evolve Vpx to recruit SAMHD1 onto the CRL4 DCAF1 E3 ubiquitin ligase in the cytoplasm for proteasome-dependent degradation, by which these viruses relieve SAMHD1-mediated restriction of primate lentivirus infection. In this review, we describe the latest knowledge of SAMHD1 biology.